Guía para la Elaboración del Estado de Flujo de Efectivo según las Normas Internacionales de Información Financieras NIIF para la Cooperativa de Ahorro y Crédito Obras Públicas Fiscales de Loja y Zamora “Coopfilz” período 2021. - Maza Jumbo, Rosa Macrina (2022)
In Ecuador, the National Financial System is formed by the Popular and Solidarity sector which has provided the best options to be competitive in the financial markets, allowing the obtainment of profitability and sustainability, thus boosting the country’s economic growth. In this research, a guide was developed for the preparation of cash flow statements according to IFRS for SMEs in Savings and Credit Cooperatives to generate cash and cash equivalents that can be useful to managers in decision-making. The Superintendency of the Popular and Solidarity Economy has proposed the Single Chart of Accounts (SCA), which establishes guidelines in the application of International Financial Reporting Standards for SMEs, so that these entities provide necessary, timely, and comparative information to their sectors at a local, national and international. This investigation had a mixed approach. Using a qualitative and quantitative method, a semi-structured interview was conducted with the person in charge of the financial department. The observation technique was used in the Cooperative’s documentation to obtain the variations of its components in the cash flow statement, with the aim of obtaining results to choose one of the methods in the application of the cash flow statement according to IFRS for SMEs in the Cooperative for Public Works for Loja and Zamora. Finally, with the preparation of the cash flow statement according to IFRS for SMEs, the managerial department of the savings and credit cooperatives are able to determine the source of cash and cash equivalents for their operating, investing, and financing activities.